Simulation-Based Interprofessional Education Terhadap Keterampilan Komunikasi Interprofesi Mahasiswa Poltekkes Kemenkes Surakarta - Syarifah Syarifah; Umy Yonaevy; Ratih Prananingrum (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Simulation-Based Interprofessional Education (SB-IPE) has emerged as an effective learning strategy by providing collaborative simulation experiences. This study aimed to analyze the effect of SB-IPE on the interprofessional communication skills of students enrolled in the Diploma III Orthotics and Prosthetics and Diploma III Occupational Therapy programs. A quasi-experimental study employing a one-group pretest–posttest design was conducted with 20 students selected through total sampling. The intervention consisted of briefing sessions, simulation of post-stroke rehabilitation cases using the SBAR communication framework, and structured debriefing. Interprofessional communication skills were assessed using the Interprofessional Collaborator Assessment Rubric (ICAR) integrated with TeamSTEPPS indicators. Data were analyzed using a paired t-test with a significance level of 5%. The mean communication score increased from 82.35 ± 8.42 before the intervention to 103.25 ± 7.96 afterward, demonstrating a statistically significant improvement (p < 0.001). The greatest improvements were observed in respect for other professions and team coordination. These findings indicate that SB-IPE effectively enhances students' interprofessional communication skills and has strong potential for integration into health professions curricula to strengthen collaborative competencies and promote patient safety.